1998
DOI: 10.1021/la971276w
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Spectroscopic Properties of Photosystem II Core Complex at the Nitrogen/Water Interface

Abstract: We have studied surface and spectroscopic properties of Photosystem II core complex (PS II CC) for the first time in monolayers at the nitrogen/water interface. A new instrument was thus specially built to perform absorption and fluorescence spectroscopic measurements directly at the nitrogen/water interface. The effect of initial surface density, incubation time, and compression speed have been studied. When PS II CC was spread at an initial surface pressure of 5.7 mN/m and immediately compressed at a speed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…14 The fluorescence micrographs of the RhC 18 monolayer at the air/water interface were obtained with the epifluorescence microscope described elsewhere. 15 The micrographs were taken in different regions of the π-A isotherm.…”
Section: Methodsmentioning
confidence: 99%
“…14 The fluorescence micrographs of the RhC 18 monolayer at the air/water interface were obtained with the epifluorescence microscope described elsewhere. 15 The micrographs were taken in different regions of the π-A isotherm.…”
Section: Methodsmentioning
confidence: 99%
“…This reduction was attributed to the fact that unfolded ␤-sheets occupy a larger area at the interface than ␣-helices. Indeed, the measurement of surface pressure-area isotherms showed that incubation of PS II CC at 0.6 mN/m leads to an increase of 1.7-4.3 in molecular area compared with when it is spread at 5.7 mN/m (Gallant et al, 1998). The PM-IRRAS signal is thus lowered as the number of amino acid residues per surface area is reduced.…”
Section: Formation Of ␤-Sheetsmentioning
confidence: 99%
“…Moreover, there is a direct thermodynamic relationship between bilayers and monolayers [126,127]. In addition, a large number of spectroscopic (UV-visible absorption [128][129][130][131][132][133][134], fluorescence [128,[131][132][133][134][135][136], and vibrational [137][138][139][140][141][142][143], (see [120,[144][145][146][147][148][149][150][151][152] for a review)), microscopic (Brewster angle [153,154] and fluorescence [155][156][157], (see [158][159][160][161][162][163][164] for a review)), and different additional physical methods [165][166][167]…”
Section: Monolayers As a Model Membrane To Study Hydrophobic Transmemmentioning
confidence: 99%